(untitled) (Research, Society and Development, 2020)
Objective of this article is to present the development of a product which was intended to improve operational conditions of the acceleration and coupling system of small boats and accessibility for users with limited financial capacity. This was achieved by reducing the mechanical wear of the traction cables (push-pull), due to the elimination of friction with the installation of electronic components and conductor cables, in order to meet the needs of boat owners as well as those of sailors. who pilot their vessels and also minimize financial expenses with maintenance and replacement of components. The product is capable of reducing the driver’s effort by 60% when activating the coupling-acceleration control, with precise couplings and smooth acceleration proportional to the control course, and allows reversibility to the conventional system (traction cables) in case of electrical failure or if the owner wants to remove the system, since it is easily uninstalled / reinstalled on another vessel, just changing the length of the conductor cable according to the vessel’s dimensions (larger or smaller). It was concluded that, this modification improves the relationship: Cost x Benefit x Operationality